2015
DOI: 10.1016/j.mce.2014.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Understanding primary aldosteronism: impact of next generation sequencing and expression profiling

Abstract: Primary aldosteronism (PA) encompasses a broad, heterogeneous group of disorders including both sporadic and familial forms (familial hyperaldosteronism type I, II and III). PA is the most common form of secondary hypertension and associated with a higher rate of cardiovascular complications, compared to essential hypertension. Despite significant progress in the diagnosis and management of PA, until recently the molecular mechanisms leading to inappropriate aldosterone production were largely unknown. The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 105 publications
(154 reference statements)
0
34
0
5
Order By: Relevance
“…KCNJ5 encodes the G protein-activated inward rectifier potassium channel GIRK4 (alternative protein name KIR3.4). All KCNJ5 mutations identified so far in APA, as well as different germline mutations identified in familial hyperaldosteronism type III (FH3) (see below), are located in exon 2; the most frequent of them are p.Gly151Arg and p.Leu168Arg, but less frequent ones located nearby have also been described (for an extensive list of identified mutations, see Gomez-Sanchez (2014) and Monticone et al (2014)). All these mutations are located near or within the selectivity filter of GIRK4, which allows selective passage of potassium ions through the channel pore, and affect the ion selectivity of the channel.…”
Section: Somatic Mutations In Apamentioning
confidence: 99%
“…KCNJ5 encodes the G protein-activated inward rectifier potassium channel GIRK4 (alternative protein name KIR3.4). All KCNJ5 mutations identified so far in APA, as well as different germline mutations identified in familial hyperaldosteronism type III (FH3) (see below), are located in exon 2; the most frequent of them are p.Gly151Arg and p.Leu168Arg, but less frequent ones located nearby have also been described (for an extensive list of identified mutations, see Gomez-Sanchez (2014) and Monticone et al (2014)). All these mutations are located near or within the selectivity filter of GIRK4, which allows selective passage of potassium ions through the channel pore, and affect the ion selectivity of the channel.…”
Section: Somatic Mutations In Apamentioning
confidence: 99%
“…7 In a large European study, the combined prevalence of APA mutations in these 4 genes was found to be 54% with 38% Abstract-Primary aldosteronism comprises 2 main subtypes: unilateral aldosterone-producing adenoma (APA) and bilateral adrenal hyperplasia. Somatic KCNJ5 mutations are found in APA at a prevalence of around 40% that drive and sustain aldosterone excess.…”
mentioning
confidence: 99%
“…1 The breakthrough was the identification of somatic mutations in the potassium channel GIRK4 (encoded by KCNJ5) in aldosterone-producing adenomas (APAs) 2 and the contemporaneous discovery, by the same authors, of a germline mutation responsible for familial hyperaldosteronism type III. 2 This was followed by the identification of further somatic mutations in APAs in 2 ATPases (Na -channel, Cav1.3 (encoded by CACNA1D).…”
mentioning
confidence: 99%
“…2 This was followed by the identification of further somatic mutations in APAs in 2 ATPases (Na -channel, Cav1.3 (encoded by CACNA1D). [1][2][3][4][5] The zona glomerulosa cells of the adrenal cortex display a high resting outward potassium current through the GIRK4 potassium channel that contributes to the hyperpolarization of the cell membrane. Most of the GIRK4 mutations identified in APA are located in or within close proximity to the selectivity filter of the K + channel and result in the indiscriminate conductance of Na + that depolarizes the cell membrane and causes the opening of voltage-gated Ca 2+ channels.…”
mentioning
confidence: 99%